2008
DOI: 10.5194/bg-5-1559-2008
|View full text |Cite
|
Sign up to set email alerts
|

Plant physiological and environmental controls over the exchange of acetaldehyde between forest canopies and the atmosphere

Abstract: Abstract. We quantified fine scale sources and sinks of gas phase acetaldehyde in two forested ecosystems in the US. During the daytime, the upper canopy behaved as a net source while at lower heights, reduced emission rates or net uptake were observed. At night, uptake generally predominated throughout the canopies. Net ecosystem emission rates were inversely related to foliar density due to the extinction of light in the canopy and a respective decrease of the acetaldehyde compensation point. This is support… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 40 publications
(63 reference statements)
2
39
0
Order By: Relevance
“…The pathways leading to both the synthesis and emission of acetaldehyde are not clear (Karl et al, 2002;Jardine et al, 2008). Acetaldehyde has long been known to be an oxidation product of ethanol produced in leaves under anoxic conditions (Kreuzwieser et al, 2000), but this cannot explain the strong emissions observed under normal environmental conditions in mid-latitude forests (e.g.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The pathways leading to both the synthesis and emission of acetaldehyde are not clear (Karl et al, 2002;Jardine et al, 2008). Acetaldehyde has long been known to be an oxidation product of ethanol produced in leaves under anoxic conditions (Kreuzwieser et al, 2000), but this cannot explain the strong emissions observed under normal environmental conditions in mid-latitude forests (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Leaf-level measurements of acetaldehyde emissions have also been found to be tightly coupled to stomatal aperture (e.g. Kreuzwieser et al, 2000;Karl et al, 2002;Niinemets et al, 2004), and it has been suggested that this may account for observed light-dependent ecosystemscale emissions of acetaldehyde (Jardine et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to Fick's law of diffusion, the VOC exchange between biosphere and atmosphere should be bidirectional depending on the concentration gradient between ambient air and the leaf interior. For some oxygenated species like acetaldehyde, which exhibit a compensation point, i.e., an ambient volume mixing ratio (VMR) at which emission turns to deposition [Kesselmeier, 2001], bidirectional fluxes are well established [Jardine et al, 2008]. In a laboratory experiment also deposition of nonoxygenated VOCs (terpenes) to plants was observed [Noe et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Although pronounced acetone, acetaldehyde and acetic acid Harley et al (1998) (the GC-MS results confirmed acetic acid rather than glycolaldehyde, also detected at the same m/z of 61 + ) peaks were observed in the spectrum, the flux of these compounds is strongly dependent on their compensation point and on the concentrations in the surrounding air. Since their concentration in the branch enclosure differs from that of ambient air, ecosystem-scale flux measurements would be preferable to estimate their fluxes (Kesselmeier et al, 1997;Schade and Goldstein, 2001;Karl et al, 2005;Jardine et al, 2008). The total counts listed in Table 2 represent 93% of the total counts in the spectrum of Fig.…”
Section: Bvoc Emissions From Ponderosa Pinementioning
confidence: 99%